Unit Usaha Syariah pada Perbankan Syariah: Tinjauan Pustaka dengan Bibliometrik - Dedy Mainata (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Islamic Banking Window have a good level of comparison and contribute to government policies in changing from Islamic business units to Islamic commercial banks. This study aims to find out which countries and their relationships with publications can be used as benchmarks for future research and present the findings of the most authored articles and provide direction for future research with the theme of Islamic Banking Window. This paper quantitatively analyzes the literature on Islamic Banking Window, as represented by English-language 60 articles from the Scopus database with a time span from 2008 to 2021. Using a bibliometric approach plus content analysis. We find that Malaysia is the most relevant country, Universiti Kebangsaan Malaysia (UKM) the most relevant institution and the International Journal of Islamic and Middle Eastern Finance and Management and Journal of Islamic Accounting and Business Research the most relevant journal. There are two main topics: (1) general studies on the Islamic banking window and (2) practical implications. We also offer future research directions.